Analysis of factors influencing delayed treatment seeking for dental caries in preschool children: a cross-sectional study - Jingsi Huang; Jiaqi Sun; Ying Ji; Chengyu Chen; Ziyuan Yang; Hong Zhao (BMC Public Health)
Abstract Objective This study investigated the prevalence of treatment delays among preschoolers with dental caries, identified the associated influencing factors, and predicted the risk of delayed treatment. The findings of this study provide an evidence base for future interventions designed to reduce treatment delays in this population. Methods A convenience sample of 264 preschool children with dental caries and their parents who visited the paediatric dental department between October 2023 and May 2024 was surveyed. Data were collected using a general information questionnaire, a medical status questionnaire, the Children’s Fear Survey Schedule-Dental Subscale, the Modified Version Dental Anxiety Scale, the Short-Form Health Literacy Dental Scale, and the Illness Perception Questionnaire Revised for Dental. Influencing factors were analysed using univariate analysis and binary logistic regression, whereas the risk of occurrence was predicted using the receiver operating characteristic (ROC) curve. Results The prevalence of delayed treatment among preschool children with dental caries was 71.21%, with an average delay of 117.5 days. Binary logistic regression analysis identified several independent factors significantly associated with delayed treatment (P < 0.05), including the primary caregiver, initial symptom recognition, children’s dental fear, parental dental anxiety, and parental oral health literacy. Predictive analyses indicated that children’s dental fear (AUC: 0.765, 95%CI: 0.707–0.823) and parental oral health literacy (AUC: 0.738, 95%CI: 0.673–0.802) demonstrated relatively high predictive values for delayed treatment. Conclusion Efforts to reduce delayed treatment should prioritise addressing children’s dental fear and improving parental oral health literacy. Targeted and effective strategies in these areas may facilitate early prevention, diagnosis, and intervention, thereby minimising treatment delays, reducing disease burden, and promoting oral health among preschoolers.